GEOMAGNETIC FIELD IN THE VICINITY OF THE PALEOZOIC-MESOZOIC BOUNDARY AND THE SIBERIAN SUPERPLUME - Pechersky D.M. (My University, 2006)
The aim of this study was to generalize the data available for the paleointensity, polarity, and frequency of reversals, and variations in the direction of the geomagnetic field in the vicinity of the Paleozoic and Mesozoic (P/T) boundary which had been marked by a peak in the magmatic activity of series superplumes, including that of the Siberian traps (251 Ma). However, no specific features have been found for the behavior of the field at that time. Some notable changes in its paleointensity had occurred 30 million years before the P/T boundary: the reversals frequency and polarity of the field changed during a period of 15 million years before the P/T boundary. The global changes of the average magnitude of the field direction variations from the unstable state with variations of 6°-10° to 6°-7° marked the lower and upper boundaries of the Kiama hyperchron (the stable state of the reversed-polarity field). The transition of the Kiama hyperchron to the Illawara hyperchron of frequent polarity changes was marked by the growth of the field variation magnitude from 6o (265 Ma) to 8°-9° (240 Ma). The regular growth of the field variation magnitude is marked with approaching to the center of Sibirian traps from the normal state, averaging 7°-8°, to 11°-12°, which demonstrated a connection between the local disturbance in the Earth core at its boundary with the mantle and the formation of the Siberian superplume. The growth of the field variation magnitude continued during a time period of 20-50 million years befor the P/T boundary and maximum activity of the Siberian trap formation, reflecting the time of the superplume rise from the base of the mantle to the Earth surface. This pattern is similar to the World magnetic anomalies, modern plumes, and the plumes in the vicinity of the Mesozoic-Cenozoic (Mz-Kz) boundary, this proving the same origin of the lower-mantle plumes and world magnetic anomalies.
Keywords: GEOMAGNETIC FIELD; PALEOZOIC-MESOZOIC BOUNDARY; SUPERPLUME; PALEOINTENSITY; Мезозой::Триасовая; Палеозой::Пермская; Mesozoic::Triassic; Paleozoic::Permian